Who is a self-initiated expatriate? Etymology, synthesis, definition - Przytuła, Sylwia; Strzelec, Gabriela (Management Sciences, 2017)
Self-initiated expatriation is a new trend in the area of expatriation that has emerged in recent years. This requires a deeper understanding because of the growing interest of international actors in this specific group of workers and the difference in their management. The interest in the topic of the SIE by both prominent academics, entrepreneurs and decision makers proves that SIEs are a valuable asset in international human resources management (IHRM). They are a measurable advantage for both the organization itself and the economies of the host countries
Nauki o Zarządzaniu = Management Sciences, 2017, Nr 4 (33), s. 23-32
Keywords: self-initiated expatriates; international worker; international human resource management; assigned expatriate; samoinicjowany ekspatriant; pracownik międzynarodowy; międzynarodowe zarządzanie zasobami ludzkimi; tradycyjny ekspatriant